On 70th Anniversary of the First Issue of Oftalmologicheskii Zhurnal (Journal of Ophthalmology (Ukraine)) - Pasyechnikova, N. V.; Vit, V.V.; Polyakova, S. I.; Zbandut, I.S. (Ukrainian Journal of Ophthalmology, 2026)
In June 2016, it will be 70 years from the first issue of the journal Oftalmologicheskii Zhurnal which was founded by academician Vladimir P. Filatov.